2021
DOI: 10.1007/s11356-021-15158-w
|View full text |Cite
|
Sign up to set email alerts
|

Review on the extraction of calcium supplements from eggshells to combat waste generation and chronic calcium deficiency

Abstract: When faced with a plethora of issues, the possibility of one problem becoming the solution of another is a rare, yet beneficial scenario. This report explores the prospect of viewing the accumulation of organic waste matter in India as a potential calcium reservoir to relieve the issue of calcium deficiency in the population. Waste generation has seen gradual growth, and it has created a problem of waste disposal. A large segment of the generated waste primarily consists of food waste which contains significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…These 0.39 million tons can hold 2542.80 tons of calcium which can supplement 6.9 million people for a year with a recommended daily allowance of 1000 mg [52]. The use of seafood waste as a source of calcium supplement was reported by Yan and Chen (2015) [53] and Singh et al (2021) [54]. Further, Kaya et al (2018) [17] reported the use of legume hulls in noodle preparation which enhanced the Ca and Mg content.…”
Section: Scope Of Seed Coat In Value Additionmentioning
confidence: 99%
“…These 0.39 million tons can hold 2542.80 tons of calcium which can supplement 6.9 million people for a year with a recommended daily allowance of 1000 mg [52]. The use of seafood waste as a source of calcium supplement was reported by Yan and Chen (2015) [53] and Singh et al (2021) [54]. Further, Kaya et al (2018) [17] reported the use of legume hulls in noodle preparation which enhanced the Ca and Mg content.…”
Section: Scope Of Seed Coat In Value Additionmentioning
confidence: 99%
“…Chicken eggshell is composed of 4% minerals and 96% calcium carbonate; so, it can be an excellent source of calcium ions [11]. Filter sand (used in the purification of water) is provided from the nearby market.…”
Section: Methodsmentioning
confidence: 99%